Integrated landslide disaster risk management (ILDRiM): the challenge to avoid the construction of new disaster risk. (27th May 2021) - Alcántara-Ayala, Irasema
ABSTRACT: There is a recognised need for bridging the gap between science and policy making aiming at the reduction of landslide disaster risk. A growing body of literature articulates the significance of scientific contributions on landslide risk assessment at different spatial–temporal scales. However, most studies in this field have mainly focused on landslide hazards, whereas vulnerability has not been treated in much detail. The present study aimed to portray the challenge involved within the integrated landslide disaster risk management sphere to avoid the configuration of new disaster risk. It should be understood whereby that landslide exposure is exacerbated by current population growth and the intensification of the use of land and resources linked to profitable activities, which in turn lead to rural transformation and a greater extent of socio-economic occupation of depreciated land in areas susceptible to hazards, urban sprawling and even expensive housing on unstable slopes. This analysis provides evidence about the need to encourage integrated landslide disaster risk management (ILDRiM), not only in the sense of reducing existing risk, but to prevent new landslide disaster risk. Thereupon, recognising and addressing landslide root causes and disaster risk drivers strongly intertwined to exposure and vulnerability should be prioritised, whereas the need of informed disaster risk governance must neither be neglected.